Inhibiting enzymatic formation of blue-green pigments in garlic cloves - DeCagna, Drew (Kansas State University, 2013)
Blue-green pigments have the ability to form in crushed and whole garlic cloves following a rapid series of enzymatic and non-enzymatic reactions. Economic losses associated with a reduction in organoleptic quality of garlic (Allium sativum L.) containing blue-green pigments can be incurred. Preventing blue-green pigment formation can mitigate potential financial and brand equity damages. To prevent pigment formation, inactivation of the enzyme which yields pigment substrates is essential. Two methods to inactivate the enzyme associated with pigment formation were explored: blanch treatment of whole garlic cloves (100°C, 5 min); and soaking of whole, non-blanched garlic cloves in low pH (<3.0) acetic or citric acid pickling solutions for seven days. The blanching treatment was effective in inactivating the enzyme as the pigment substrate decreased by approximately 99% as compared with pigment substrate concentrations in non-blanched garlic cloves. Soaking whole garlic cloves in low pH (<3.0) pickling solutions did not result in enzyme inactivation as pigments formed in cloves soaked in the acetic acid pickling solutions; however pigments did not form in cloves soaked in the citric acid pickling solution. This may be due to the different effect mono- and poly-carboxylic acids have on the permeability of garlic cell membranes. Blanching garlic cloves can be implemented as a processing step to prevent pigment formation. Soaking garlic in a low pH pickling solution comprised of a poly-carboxylic acid does not inactivate the enzyme associated with pigment formation but pigment formation can be prevented. Other methods presented in the literature to prevent pigment formation include controlling growth, harvest and storage conditions, as well as treating garlic clove homogenates with chemical additives.
Keywords: Garlic; Pigment; Enzyme; Blue; Green; Inhibiting; Food Science (0359)